2019
DOI: 10.1017/ice.2019.15
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study of antibiotic exposure and vancomycin-resistant Enterococcus recolonization

Abstract: Objective:In the National Institutes of Health (NIH) Clinical Center, patients colonized or infected with vancomycin-resistant Enterococcus (VRE) are placed in contact isolation until they are deemed “decolonized,” defined as having 3 consecutive perirectal swabs negative for VRE. Some decolonized patients later develop recurrent growth of VRE from surveillance or clinical cultures (ie, “recolonized”), although that finding may represent recrudescence or new acquisition of VRE. We describe the dynamics of VRE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Another study reported not only re-colonization of VRE after hematopoietic stem cell transplantation but also showed that exposure to antimicrobials may increase the likelihood of re-colonization ( 14 ). Our patient's rectal swab cultures remained negative despite the administration of piperacillin/tazobactam and cefepime for urinary tract infection four months after decolonization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported not only re-colonization of VRE after hematopoietic stem cell transplantation but also showed that exposure to antimicrobials may increase the likelihood of re-colonization ( 14 ). Our patient's rectal swab cultures remained negative despite the administration of piperacillin/tazobactam and cefepime for urinary tract infection four months after decolonization.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the regimen followed in this case markedly decreased the intestinal bacterial load of VRE. As mentioned in several studies, clearance of VRE colonization is controversial, and it may take up to three or four consecutive negative cultures one or more weeks apart to identify successful decolonization ( 5 , 7 , 13 , 14 ). Thus, to confirm successful decolonization, we obtained rectal swab cultures until six months after decolonization, as previously reported ( 6 ), using a selective medium with increased sensitivity of detection.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Overdiagnosis of CDI leads to overtreatment, which leads to concern of overgrowth of vancomycin-resistant enterococci, development of antimicrobial resistance and increased risk of future development of CDI through gut dysbiosis. 35 38 …”
Section: Reviewmentioning
confidence: 99%
“…34 Overdiagnosis of CDI leads to overtreatment, which leads to concern of overgrowth of vancomycinresistant enterococci, development of antimicrobial resistance and increased risk of future development of CDI through gut dysbiosis. [35][36][37][38] Antimicrobial and diagnostic stewardship are also important for the prompt and appropriate management of BSIs, which are often associated with sepsis. Studies have shown the importance of diagnostics to improve the time to appropriate therapy in sepsis and its association with improved mortality.…”
Section: Reviewmentioning
confidence: 99%
“…VRE colonization has been noted to precede VRE infection. In particular, among immunocompromised patients including hematopoietic stem cell transplantation, not only VRE colonization is hard to eradicate after initial colonization, but also recolonization occurs in 29% of patients, further raising the risk of VRE infection in this vulnerable patient population [17,22,24]. Given the data linking oral vancomycin and metronidazole to new VRE stool colonization, a focus on diagnostic stewardship and efforts to discontinue therapy in patients without CDI should be prioritized to mitigate the risk of developing VRE colonization or infection.…”
Section: Impact Of Overdiagnosismentioning
confidence: 99%